THE USE OF DIGITAL VLOGGING TO ENHANCE THE REVIEW TEXT SPEAKING SKILL OF THE TWELFTH GRADERS OF SMAK PENDOWO MAGELANG IN THE SCHOOL YEAR 2018/2019 - Agnes Amalia Puspita (Faculty of Education and Teachers Training, 2019)
Internet and information technology can be used for English learning process since they provide a chance to improve students’ ability in English. One of the activities which can be used as a technique in learning speaking skill is digital vlogging. The objectives of this research are to know how great can the use of digital vlogging enhance students’ interest to the review text speaking skill of the twelfth graders of SMAK Pendowo Magelang in the school year 2018/2019 and to know how great is the enhancement of review text speaking skill of the twelfth graders of SMAK Pendowo Magelang in the school year 2018/2019 by using digital vlogging. This study is a classroom action research. It was conducted in SMAK Pendowo Magelang. The subjects of the research were the XII IPA students of SMAK Pendowo Magelang in the school year 2018/2019. The types of the data are quantitative and qualitative data. The quantitative data were obtained from tests and they were in the form of students’ scores. Meanwhile, the qualitative data were collected through observation, questionnaire, and documentation. Digital vlogging brings great enhancement to the students’ interest and the enhancement of review text speaking skill is great. It can be inferred that all implemented actions are successful to enhance the students’ interest and students’ speaking skill of review text. Digital vlogging also makes everyone consider that learning is fun and it increases students’ confidence in speaking English.